A New Antirotation Strategy of K-Wire Tension Band Therapy for Patellar Fracture - Sun, Fengpo; Zhang, Yawen; Ji, Quan; Zhang, Tongyi; Zhu, Yi; Zhang, Ze; Han, Ruining; Wen, Liangyuan (Frontiers in Surgery, 2022)
Background Patellar fracture is a common phenomenon observed in orthopedic clinics. Many methods have been shown to be effective in the fixation of patellar fracture. However, there are few studies on the antirotation effect of these methods. The purpose of this study is to present a new strategy of K-wire tension band therapy for patellar fracture and explore the antirotation effect of the modified tension band method on patellar fracture. Methods A retrospective clinical observation study was conducted on 75 patients with patellar fracture. Totally, 46 patients were enrolled to the traditional group, who received the traditional K-wire tension band therapy. The modified group included 29 patients on whom our new strategy was implemented. The operation time, intraoperative blood loss, and fracture healing time were collected to compare the two operations and the knee society score (KSS) scores after the operations, and complications were recorded and retrieved to indicate the effectiveness of the two treatments. Results The preoperative baseline data (gender, age, fracture types) of the two groups showed no significant statistical difference. Similarly, there was no significant difference in the operation time, intraoperative blood loss, and fracture healing time between the two groups. The KSS clinical scores 1 year after operation was 90 (84, 95) for the traditional group as compared with 99 (97, 100) for the modified group (p < 0.05). The KSS functional scores 1 year after operation in the two groups were 90 (65, 90) and 100 (90, 100) (p < 0.05). The incidences of complications due to the rotation of K-wires in the traditional group and the modified group were 76.1% (35 of 46) and 6.9% (2 of 29) with a significant statistical difference (p < 0.05). Conclusion This study shows that our modified tension band therapy is an effective strategy for antirotation in the treatment of patellar fracture and proves that it can achieve better clinical outcomes than the traditional K-wire tension band method. This new strategy may be a safe and effective clinical technique for the treatment of patellar fracture. However, more prospective randomized controlled trials with larger sample sizes are still needed to further prove its efficacy.